Особливості відновлення, збереження та підвищення коефіцієнту життєвої енергії лідера - Тіняков, Артем Олександрович (НТУ "ХПІ", 2017)
Розглянуто особливості системи підготовки лідерів, обґрунтовано важливість та необхідність розвитку окремих складових освіти лідера, зокрема коефіцієнту життєвої енергії VQ. Розкрито складові життєвої енергії та сутність потенційної та реальної життєвої енергії. Запропоновано підходи для збереження та підвищення енергетичного потенціалу лідера, приближення реального рівня його VQ до природнього (потенціального). За результатами аналізу опрацьовано рекомендації щодо підвищення енергетики лідера, гармонізації та збалансування його життєвої енергії.

The relevance of the article is to find ways to improve the effectiveness of training leaders. Features of the system for training leaders are considered, one of the most important conditions of which is a harmonious combination of intellect, emotional intelligence and spiritual intelligence. A high level of development of these components is a necessary, but insufficient condition for the leader's effectiveness. The most important indicator is the vital energy of the leader (VQ), which determines the ability to charge yourself and others with creative energy. The components of the concept of the vital energy VQ are revealed and its significance is shown in the structure of the preparation of a successful leader. The importance and necessity of development of separate components of education of the leader, in particular the coefficient of vital energy VQ, is grounded. The necessity of restoration, preservation and increase of the life-energy coefficient of the leader is substantiated.
Features of restoration, preservation and improvement leader’s vitality coefficient
Keywords: підготовка лідерів; лідерство; потенційна життєва енергія; енергетика лідера; leadership; potential vitality